The globalizers : the IMF, the World Bank, and their borrowers - Woods, Ngaire (Cornell studies in money., 2006)
"The greatest success of the International Monetary Fund and the World Bank has been as globalizers. But at whose cost? Would borrowing countries be better off without the IMF and World Bank? This book takes readers inside these institutions and the governments they work with. Ngaire Woods decodes what they do and why they do it, using original research, extensive interviews carried out across many countries and institutions, and scholarship from the fields of economics, law, and politics."--Jacket